Wellness, muscle soreness and neuromuscular performance during a training week in volleyball athletes - Tavares, F.; Simoes, M.; Matos, B.; Smith, T. B.; Driller, M. (The Journal of Sports Medicine and Physical Fitness, 2018)
BACKGROUND: The purpose of the current study is to analyze the acute effects of volleyball training and to compare the responses of different perceptual and neuromuscular measures to overall training load. METHODS: The training load, wellness, neuromuscular performance and perceptual measures of soreness of 13 highly-trained volleyball athletes (18±1 years; 187.1±7.0 cm; 84.3±10.3 kg) representing the Portugal under-19 national team were monitored during a training week. Perceptual fatigue was obtained in the morning of every training day from a 5-item wellness questionnaire (sleep, soreness, mood, fatigue, stress) and a muscle soreness questionnaire surveying nine different muscle sites from each side of the body. Neuromuscular performance was obtained from a countermovement jump (CMJ) on the morning of training days 1, 2, 4, and 5. RESULTS: Small effect sizes in CMJs were observed on days 4 and 5 when compared to baseline. Wellness items were affected by training, with the fatigue item and the total score being the most affected. Muscle soreness increased from day 2 until day 5 in comparison to baseline across various muscle sites and regions. Nevertheless, responses in soreness were different from muscle sites, average of muscle sites and a single question of muscle soreness. CONCLUSIONS: Volleyball training elicits meaningful changes in physiological and perceptual measures of fatigue and muscle soreness, as evident from day 2 until the last training day of the week. Muscle soreness scores obtained from different muscle sites may provide important information to coaches.